Research on the Influence of Some Fertilization Variants on Maize Yield - Ana-Maria Valean; Adina Tarau; Laura Sopterean; Florin Russu; Alina Simon; Ioana Crisan; Loredana Suciu (Journal of Agriculture and Rural Development Studies, 2024)
Green manures can improve soil structure through nutrient growth, but also crop production, playing an important role in sustainable agriculture. The objective of this study is to research the effect of different cover crops as green manure on maize yield. The experience was located at the Agricultural Research and Development Station Turda and included multiple variants of maize fertilization, which was sown on three agro-funds: classic and after the incorporation of crops used as green manures, namely lupine and phacelia. From the results obtained through this study, it can be seen that the highest maize yields (6,045 kg/ha) were obtained when the maize was sown after the incorporation of lupine, in the variant where ammonium nitrate was additionally applied.